Genetic analysis of microsatellite markers for salt stress in two contrasting maize parental lines and their RIL population - (:unkn) unknown (UNIV ZAGREB, FAC SCIENCE, DIV BIOLOGY, 2017)
Salt stress considerably hinders the growth and productivity of maize (Zea mays L.). Identifi cation of salt tolerant genotypes and integration of alternative molecular markers have important roles in enhancing breeding processes. In this study, 3308 maize expressed sequence tags (ESTs) from salt stress-related libraries were assembled to mine repetitive sequences for development of applicable markers. In this core EST data, 208 simple and 18 non-simple repetitive regions were detected in 312 contigs and 1121 singletons. The di-nucleotide repeats were the most abundant type and accounted for 79.3%, followed by tri (19.7%), and tetra-nucleotide (1%). Among 59 EST-simple sequence repeats (SSRs), a total of 55 were screened for polymorphism between F35 (salt sensitive) and F63 (salt tolerant) parents and 48 out of 55 were detected as monomorphic. Signifi cantly, seven of them (12.7%) were found to be polymorphic and were used for genotyping of 158 F5 derived recombinant inbred maize lines, and four of them were located on chromosome 1 and 3. Using in silico mapping, 44 out of 59 EST-SSR markers were mapped on 10 maize chromosomes. Analysis of sequence homology revealed different functional groups such as: membrane transport, cell defense, cell division, signaling components, photosynthesis and cell metabolism. These EST-SSRs might be used as new functional molecular markers in the diversity analysis, identifi cation of quantitative trait loci (QTLs) and comparative genomic studies in maize in the future.
Keywords: EST; maize molecular markers; salinity; SSR; LIPID TRANSFER PROTEINS; MAP; IDENTIFICATION; TOLERANT; REPEATS; SORGHUM; RICE; SSR; ENVIRONMENT; SOFTWARE